Therapy for Cerebral Palsy by Human Umbilical Cord Blood Mesenchymal Stem Cells Transplantation Combined With Basic Rehabilitation Treatment: A Case Report. (5th March 2015) - Zhang, Che; Huang, Li; Gu, Jiaowei; Zhou, Xihui
Background . Cerebral palsy (CP) is the most common cause leading to childhood disability. Human umbilical cord blood mesenchymal stem cells (hUCB-MSCs) transplantation is a promising alternative considering the safety and efficacy in current reports. This report represents a case of hUCB-MSCs transplantation combined with basic rehabilitation treatment beginning as early as age 6 months with follow-up as long as 5 years. Methods . A 6-year-old female patient was diagnosed with CP at age 6 months. The patient accepted 4 infusions of intravenous hUCB-MSCs in each course and received 4 courses of transplantation totally. A series of assessments were performed before the first transplantation, including laboratory tests, CDCC Infant Mental Development Scale, and Gross Motor Function Measure-88 (GMFM-88). Then annual assessments using the GMFM-88, Ashworth spasm assessment, and comprehensive function assessment scale were made in addition to the annual laboratory tests. In addition, electroencephalography and brain magnetic resonance imaging were conducted before transplantation and in the follow-up phase. Rehabilitation and safety follow-up have been ongoing for 5 years up to date. Results . There was no complaint about adverse effects during hospitalization or postoperative follow-up. Motor function recovered to normal level according to the evaluation of scales. Language function improved significantly. Linguistic rehabilitation therapy was enhanced for further improvement. Conclusions . The clinical application of hUC-MSCs combined with basic rehabilitation treatment was effective and safe for improving motor and comprehensive function in a patient with CP.